MUTU GURU DALAM PEMBELAJARAN MELALUI PENERAPAN SUPERVISI KLINIS DI SDN 014/XI PELAYANG RAYA - Aznur Aznur (STKIP Pesisir Selatan, 2018)
This study started from the low quality of education, especially in SDN 014 / XI Pelayang Raya District Sungai Bungkal Sungai Penuh River. The purpose of this research is to know the application of principal clinical supervision at SDN 014 / XI Pelayang Raya Kecamatan Sungai Bungkal to improve teacher quality in learning process Year 2016/2017.The subjects in this study were Teachers SDN 014 / XI Pelayang Raya Kecamatan Sungai Bungkal which is where the researcher served as head of school year 2016/2017. Action is implemented in 3 cycles. Activity is carried out in even semester of academic year 2016/2017. Duration of 6 weeks effective study conducted from 5 September to 17 October 2016. In the implementation of the action, the design is done in 3 cycles that include; (1) planning, (2) action, (3) observation, (4) reflection. In the data collection techniques used are to use observations and questionnaires. Based on the results of the above research, improving the quality of teachers in the learning process, through the guidance of clinical supervision is very good result. This was apparent at the first meeting of the 11 teachers who were present at the time of the study; 67.73% increased to 71.27% and in cycle 3 increased to 75.91%. Based on the Ministerial Regulation No. 12 of 2007 on the competence of teachers and principals, and can make school work plans, and can organize schools towards the desired changes reach 85% achievement, then the clinical supervision is said to be effective. Thus the hypothesis proposed above is acceptable